ANALYSIS OF SUPREME COURT DECISION NO.556/Pdt.G/2022 - Guisepino Bakito Obe; Virgi Faisya Adhazia; Shelby Yoga Pratama; Aprilia Princes Gray; Jeny Aprilia (President University, 2023)
This study examines a breach of contract case involving PT. Hasana Damai Putra and Gregorius Harison S, focusing on the court's role in delivering justice and resolving disputes. The case centers on the defendant's failure to fulfill obligations outlined in a property purchase agreement, resulting in financial losses for the plaintiff. The verdict by the Bekasi District Court deemed the defendant's actions as constituting breach of contract, annulling the agreement and ordering compensation for the plaintiff's damages. Using qualitative normative legal research, this analysis explores factors influencing judicial decisions, including factual assessments, legal interpretations, moral considerations, and social contexts. The court's decision, grounded in plaintiff-provided evidence and meticulous legal analysis, underscores its commitment to upholding contractual obligations and ensuring fairness in legal proceedings. Moreover, it highlights the judiciary's role in protecting individual rights and fostering societal stability. This study underscores the importance of court rulings in providing legal clarity, safeguarding rights, and bolstering public confidence in the legal system. By adhering to principles of justice and applicable laws, court decisions serve as vital tools in resolving disputes, fostering social cohesion, and upholding the rule of law. Therefore, this case serves as a poignant illustration of the judiciary's pivotal role in dispensing justice and maintaining legal order within society.Keywords:Breach of contract, Judicial decision-making, Legal analysis, Dispute resolution,Court verdict, Contractual obligations